Factors affecting the perception of plosives in second language English by first language Cypriot-Greek listeners - Kkese, Elena; Petinou, Kakia (My University, 2017)
This paper investigates the difficulties adult second language users of English encounter with plosiveconsonants. It presents the results of a word identification task examining the acquisition of plosive voicingcontrasts by college students with Cypriot-Greek background. The task by using minimal pair words focused oninvestigating possible factors affecting plosive identification. Both descriptive and inferential analyses wereused for identifying how important each factor is when it comes to plosive consonants. The results provide anindication of the rank order for the examined factors. Specifically, syllable position is identified as having thegreatest influence on plosive identification, followed by voicing, word position, and place of articulation forboth kinds of analyses. By accepting the hypothesis that less successful differentiation of plosive consonants inthe second language on the part of Cypriot-Greek users was partially due to the investigated factors manifestedimplies that the specific second language sounds do not exist or are non-contrastive in the first language.Nonetheless, because the weighting of auditory cues in the categorisation of plosives is language-specific,participants were modifying their identification of voiced plosives to fit the mother tongue. Speech perceptioncan, therefore, account for the data of the present study. Specifically, Voice Onset Time provides importantinformation to the voiceless-voiced distinction as well as word-initial, syllable onset plosive consonants. Takentogether, the results of the present study indicate that when dealing with contrastive categories in the secondlanguage, the acoustic cue of Voice Onset Time is of crucial importance. For Cypriot-Greek users, acquiringvoiced plosives means acquiring new Voice Onset Time patterns.
Keywords: plosive consonants; voice onset time; second language; speech perception